Epidemiology, causes, and treatment of epilepsy in sub-Saharan Africa. - Ba-Diop, A; Marin, B; Druet-Cabanac, M; Ngoungou, E; Newton, C; Preux, P (Lancet, 2014)
SUMMARY: Epilepsy is a common neurological disease in tropical countries, particularly in sub-Saharan Africa. Previous work on epilepsy in sub-Saharan Africa has shown that many cases are severe, partly a result of some specific causes, that it carries a stigma, and that it is not adequately treated in many cases. Many studies on the epidemiology, aetiology, and management of epilepsy in sub-Saharan Africa have been reported in the past 10 years. The prevalence estimated from door-to-door studies is almost double that in Asia, Europe, and North America. The most commonly implicated risk factors are birth trauma, CNS infections, and traumatic brain injury. About 60% of patients with epilepsy receive no antiepileptic treatment, largely for economic and social reasons. Further epidemiological studies should be a priority to improve understanding of possible risk factors and thereby the prevention of epilepsy in Africa, and action should be taken to improve access to treatment.